Examining the effect of group investigation cooperative learning on student science achievement and collaboration skills - Erna Kusumawati; Wahyu Edi Prasetyo; Ikah Salhah (HAMKA INSIGHT, 2026)
Purpose: This study evaluates the pedagogical efficacy of the six-stage Group Investigation cooperative learning model on primary students' science achievement and collaboration skills, directly addressing cognitive and affective limitations associated with conventional teacher-directed instructional approaches in elementary science education. Method: Employing a six-week quantitative, quasi-experimental pretest-posttest control group design, the research involved elementary students across intact classrooms. Data were gathered using a validated Science Achievement Test measuring higher-order cognitive domains alongside a dual-mode Collaboration Evaluation Framework comprising peer assessments and direct observations. Data were processed using multivariate and univariate analyses of covariance to control for baseline differences. Findings: Multivariate analysis revealed a highly significant positive effect for Group Investigation on combined cognitive and interpersonal outcomes. Follow-up univariate testing demonstrated substantial, statistically significant gains in conceptual science mastery and peer collaboration skills compared to direct instruction, with high partial eta squared effect sizes confirming practical significance. Practical implications: Findings provide elementary educators and curriculum designers with an actionable, scalable framework to simultaneously cultivate essential twenty-first-century collaboration competencies and deep conceptual science understanding. Originality/value: This research offers novel empirical validation regarding scaffolded group investigation in primary education, demonstrating its capacity to bridge cognitive academic mastery and socio-emotional learning.